DETERMINANT ANALYSIS OF FINANCIAL SECTOR STOCK IN INDONESIA STOCKS EXCHANGE - Yusmia, Liza; Asianto, Abitur (Dinasti Publisher, 2020)
These research had purposed to examine related to macroeconomic variables on financial sector stock index in Indonesia Stock Exchange. This research used Vector Error Correction Model (VECM) method with monthly data from financial sector stock index as the dependent variable and the GDP quarterly data, as well as monthly data on inflation, BI interest rates, exchange rates, the Fed interest rate, gold prices, oil prices,and also the S&P 500 index as independent variable with data range from January 2014 to August 2019. These results that obtained from this research were the shocks in BI interest rate variable and the exchange rate which have positive responses in the long term, while the GDP, inflation, and Fed interest rates , gold prices, oil prices, and the S&P 500 index responded negatively in the long term by the financial sector stock index. Beside that, the BI interest rate variable has the greatest contribution in changed of financials stock index.